The Dynamic Modeling of a Bird Robot - Couceiro, Micael S. (2019)
This paper presents the development of computational simulation and a robotic prototype based on the dynamic modeling of a robotic bird. The study analyze the bird flight with different strategies and algorithms of control. The results are positive for the construction of flying robots and a new generation of airplanes developed to the similarity of flying animals. A bird robot prototype was implemented based on materials used to construct model planes. It consists on a body, wings and tail with servo actuators independently controlled though a microcontroller; a radio transmission system and batteries were also used in order to avoid wired connections between the computer and the robot.